Psychometric properties of the BIRT Motivation Questionnaire (BMQ), a self-measure of avolition in individuals with schizophrenia. (March 2022) - Raffard, Stéphane; Norton, Joanna; Van der Linden, Martial; Lançon, Christophe; Benoit, Michel; Capdevielle, Delphine
Abstract: Aims: Avolition defined as a lack of interest or engagement in goal-directed behavior plays a key role in everyday functioning in schizophrenia and is considered as one of the main contributors to the burden of disease. The aim of this study was to 1) validate the self-report BIRT Motivation Questionnaire (BMQ-S) seldom used before in schizophrenia 2) examine the degree of agreement between the BMQ-S and its informant-report version 3) to assess its ability to predict real-world outcome at 12 month follow-up. Methods: One hundred and twenty-two (51.9% inpatients) adults with a diagnosis of schizophrenia were included. Exploratory Factor analysis was performed on the BMQ-S to identify the underlying structure. Real life functioning was measured with the Global Assessment of Functioning scale (GAF). Convergent validity was assessed with the Scale for Assessment of Negative Symptom (SANS) and the Lille Apathy Rating Scale (LARS). Results: The main psychometric properties of the BMQ-S (internal consistency, test-retest reliability) were satisfactory. Exploratory factorial analysis revealed a 4-factor model which explained 76% of the overall variance. The BMQ-S correlated significantly with the LARS and the SANS avolition subscore suggesting adequate convergent validity. The correlation between the BMQ-S and the clinician-report version was 0.48. The global score and in particular the Initiation/disorganisation dimension was a significant predictor of global functioning at 12-months even when adjusted for age, chlorpromazine intake and depression. Conclusion: Our findings indicate that the BMQ-S has satisfactory psychometric properties and that schizophrenia patients can reliably assess their lack of motivation. Self-evaluation of avolition should be considered in the overall prediction of real-world functioning in schizophrenia.